2014
DOI: 10.1186/s12879-014-0727-5
|View full text |Cite
|
Sign up to set email alerts
|

The microbiology of impetigo in Indigenous children: associations between Streptococcus pyogenes, Staphylococcus aureus,scabies, and nasal carriage

Abstract: BackgroundImpetigo is caused by both Streptococcus pyogenes and Staphylococcus aureus; the relative contributions of each have been reported to fluctuate with time and region. While S. aureus is reportedly on the increase in most industrialised settings, S. pyogenes is still thought to drive impetigo in endemic, tropical regions. However, few studies have utilised high quality microbiological culture methods to confirm this assumption. We report the prevalence and antimicrobial resistance of impetigo pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 30 publications
(31 reference statements)
4
64
1
Order By: Relevance
“…It is unlikely that this difference in treatment success is driven by the presence of MRSA in children with scabies, as there was no increased association between MRSA and scabies detection observed in logistic regression models. 22 The only microbiological association with the presence of scabies in the trial was an increased chance of detecting S. pyogenes (odds ratio, 2.2; 95% CI: 1.1-4.4%). 20 Microbiology alone cannot explain this difference in treatment success.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is unlikely that this difference in treatment success is driven by the presence of MRSA in children with scabies, as there was no increased association between MRSA and scabies detection observed in logistic regression models. 22 The only microbiological association with the presence of scabies in the trial was an increased chance of detecting S. pyogenes (odds ratio, 2.2; 95% CI: 1.1-4.4%). 20 Microbiology alone cannot explain this difference in treatment success.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study found no increased association between methicillin-resistant S. aureus (MRSA) and scabies detection. 22 Most children (463/508; 91.0%) were located in the tropical region, known as the Top End with (45/508; 9.0%) living in Central Australia, a desert climate. Scabies prevalence was 17.8% in the Top End and 16.5% in Central Australia, P = 0.47.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore the demonstrated frequency of co-infection of S. pyogenes with S. aureus and the emergence of CA-MRSA present additional challenges in selecting appropriate therapy. 5,6 Antibiotic treatment of affected individuals leads to resolution of impetigo lesions which likely reduces transmission. Studies to date have not explored the effect of antibiotics on rarer endpoints such as invasive infection or APSGN due to the large sample size required.…”
Section: Limited or Uncomplicated Impetigomentioning
confidence: 99%
“…Bacterial infection, particularly with S. pyogenes and S. aureus, is a well-recognised complication of scabies infestation. 1,4,5,13 The presence of scabies is associated with complications of impetigo including invasive bacterial infection and post-streptococcal glomerulonephritis. 11,13,14 As discussed earlier, in endemic settings the treatment of scabies at a community level has been shown to reduce the prevalence and severity of skin sores 32 and haematuria.…”
Section: Clinical Manifestations Complications and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation